Maclaurin on Occasionalism: A Reply to Ablondi. Issue 1 (March 2016) - Connolly, Patrick J.
Abstract : In a recent article Fred Ablondi compares the different approaches to occasionalism put forward by two eighteenth-century Newtonians, Colin Maclaurin and Andrew Baxter. The goal of this short essay is to respond to Ablondi by clarifying some key features of Maclaurin's views on occasionalism and the cause of gravitational attraction. In particular, I explore Maclaurin's matter theory, his views on the explanatory limits of mechanism, and his appeals to the authority of Newton. This leads to a clearer picture of the way in which Maclaurin understood gravitational attraction and the workings of nature.